Equity in Essential Maternal, Newborn, and Child Health Interventions in Northeastern China, 2008 to 2018 - Wang, Ying; Liao, Ran; Feng, Xing Lin (Frontiers in Public Health, 2020)
Objectives We aim to analyse equity in maternal, newborn and child health (MNCH) interventions in Jilin, a north-eastern province of China, 2008 to 2018. Study design Cross-sectional study Methods We used provincially representative survey data in 2008, 2013 and 2018. We included 18 essential MNCH interventions, analysed equity and calculated the composite coverage score. We used logistic and multiple linear regressions to adjust sampling clusters and covariates. Results Coverage of hospital-based interventions, such as hospital delivery and antenatal B-ultrasound tests, was nearly universal in Jilin Province. Caesarean sections persisted at alarmingly high rates (57.6%). Enormous unmet needs and rural-urban inequalities existed for community-based interventions such as improved drinking water sources (85.4% vs. 97.9%, p<0.01), improved sanitation facilities (52.5% vs. 94.2%, p<0.01), four government-funded antenatal care services (55.8% vs. 84.1%, p<0.01), and at least 8 antenatal care sessions (26.8% vs. 46.3%, p<0.05). Compared to rural-urban inequity, individual-level disparities across income and education were either small in scale or statistically insignificant. The inequity in coverage of maternal and newborn care shrank during 2008-2018. Conclusions Despite its success in reducing mortality, China’s unique obstetrician-led safe motherhood strategy may come at the cost of over-medicalisation and health inequity. Jilin Province’s recent efforts to revitalise primary health care show the potential to make a change. An integrated system that links families, communities and all levels of health care organisations seems to be the most effective and efficient model to offer continuing MNCH care.